Perancangan Motif Topeng Dengan Teknik Batik Cap Berbahan Kertas Untuk Cardigan - Intania, Nur Annisa; Affanti, Tiwi Bina (Pusat Penerbitan LPPM ISI Bali, 2024)
This design is motivated by young people who currently have difficulty learning about batik and a culture that is almost extinct in Yogyakarta. Today's young people find batik difficult to work on considering the time it takes to make batik, especially written batik. One of the cultures in Yogyakarta which is currently almost extinct is Wayang Topeng Wayang. This culture is almost extinct due to the rarely played by the puppeteer's family. The purpose of this design is to provide an easy way for young people to learn batik and to make batik cardigans from paper stamps with motifs from Wayang Topeng Pedalangan Yogyakarta. The design of this cardigan product applies the art design approach according to SP. Gustami, who put forward 3 stages and 6 steps in the creative process. The three stages are the exploration or data collection stage, the design or sketching and design, the last is embodiment. The results of this design are as follows: (1) Dancer motifs, puppeteer motifs, and musician motifs are used as the main motifs with supporting motifs inspired by the ornaments in the saron in the form of leaves, flowers, and mlungker. (2) The product is made into a cardigan for middle class women aged 20-30 years. The cardigan uses stamped batik technique with remasol dab coloring. The cardigan material is Japanese cotton fabric.